Thyroid Troubles Unveiled: A Rare Case of Hyponatremia Secondary to Hypothyroidism - Abdul Razack, Jafrin Sadiq; Hussaini, Syeda Juveria; Khaled Aldoseri, Saud; Asgar Ali, Sahil; Elnaily, Mohamed (International Journal of Innovative Research in Medical Science, 2024)
Thyroid hormones, produced by the thyroid gland, play various roles in the body. Essential for fetal development. There are many complications, one of which is rare: hyponatremia, an electrolyte imbalance characterized by low levels of sodium in the body. We present a case of a 69-year-old man who arrived at the emergency department after falling from the sofa and experiencing subsequent memory loss. The sodium level upon arrival was 114 mmol/L. After ruling out other potential causes of hyponatremia, the final diagnosis was hypothyroidism. After treating hypothyroidism, the sodium level began to rise again. It is essential to check thyroid function when a patient with low sodium and clinical symptoms of altered mental status is admitted to the hospital.